The association between the inflammatory response to surgery and postoperative complications in older patients with cancer; a prospective prognostic factor study. Issue 5 (June 2020) - Plas, Matthijs; Rutgers, Abraham; van der Wal-Huisman, Hanneke; de Haan, Jacco J.; Absalom, Anthony R.; de Bock, Geertruida H.; van Leeuwen, Barbara L.
Abstract: Background: Accurate prognostic biomarkers would substantially improve surgical planning and decisions making yet no studies have been reported exploring the inflammatory response in surgically treated older patients with cancer. The aim of this study was to explore inflammatory biomarkers as potential prognostic factors for postoperative complications within 30 days in older patients with cancer. Method: Patients 65 years and older undergoing surgery for removal of a solid malignant tumour were included in an observational cohort study. All complications occurring up to 30 days postoperatively were documented prospectively. Inflammatory markers were measured in plasma samples pre- and postoperatively: C-reactive protein (CRP), Interleukin-1 beta (IL-1β), IL-6, IL-10, IL-12, and Tumour necrosis factor-alpha (TNF-α). Associations between inflammatory markers and postoperative complications were explored using logistic regression analysis. Results: Between July 2010 and April 2014, plasma samples of 224 patients were collected. Median age was 72 (65–89) years and 116 (51.8%) patients were female. Approximately half of the patients developed postoperative complications (49.6%) of whom 62 patients (55.9%) developed >1 complication. An independent prognostic effect was observed for the inflammatory biomarkers IL-6 and IL-10 for the occurrence of postoperative complications. Conclusion: The perioperative inflammatory response is associated with complications, independently from patient and surgical factors which are also associated with outcome. Research is warranted towards further exploration of the perioperative inflammatory response with the aim to improve perioperative care and outcome, and might help to improve surgical planning and decision making for older patients with cancer. Highlights: Nearly half of the older patients with cancer develop postoperative complications. The inflammatory response is associated with postoperative complications. Of all postoperative complications, 42.4% were considered inflammatory in nature.